Policy Implementation of The Electronic Traffic Law Enforcement in The Greater Jakarta Metro Area Police Jurisdiction - Louis Bisma Wicaksana Praharsa; Muh Azis Muslim; Kusuma, Reyhan; Arisandi, Azel (Jurnal Ilmu Kepolisian, 2024)
The aim of this study is to investigate the implementation of the ETLE policy in the Greater Jakarta Metro Area Police Jurisdiction. Data has shown that there have been fluctuations in the trend of traffic violations in the Greater Jakarta Metro Area Police Jurisdiction from 2018-2023. This research examines further the implementation of the Electronic Traffic Law Enforcement (ETLE) policy to realize an orderly traffic area in the Greater Jakarta Metro Area Police Jurisdiction. Researchers use Grindle's policy implementation model to look at policy implementation. The researchers used a post-positivist approach by conducting data analysis techniques using illustrative methods on primary data in the form of in-depth interviews. In-depth interviews were conducted with several crucial policymakers, including the Traffic Director at the Greater Jakarta Metro Area Police, who led the ETLE policy in its jurisdiction. The results showed that implementation of the ETLE policy in the Greater Jakarta Metro Area Police jurisdiction has not run optimally in establish an orderly traffic area. Although there is progress in implementation, there are several critical notes that must be addressed to achieve policy objectives.